DETERMINATION OF ARGININE AND ASCORBIC ACID IN EFFERVESCENT TABLETS BY MULTIDIMENSIONAL CHROMATOGRAPHY - Andrea E. Rech; Cristina P. Farina; Pamela C. Lukasewicz Ferreira; Diogo Miron (Drug Analytical Research, 2017)
This paper describes a fast and direct method for quantification of arginine and ascorbic acid (vitamin C) in effervescent tablets. HPLC-UV multidimensional chromatography (RP18 and cyanopropyl columns) was developed and validated. Phosphate buffer 10 mMpH 3.4 was used as mobile phase. Satisfactory resolution between the drugs was obtained with analysis time less than 8.0 min. Method was linear in the ranges of 140-320 mg.mL-1 and 240-560 mg.mL-1 for arginine and ascorbic acid, respectively. Precision showed RSD <2.0%. Recovery was 99.5% and 100.0% for arginine and ascorbic acid, respectively. Robustness was confirmed through factorial analysis 22 (pH and mobile phase flow rate as factors).